Relationship Between Duration of Exclusive Breastfeeding and Cognitive Development in Children: A Systematic Study - Ruth Olivia Widianto; Johannes Cancius Prihadi; Ellen Wijaya; Laurentius Aswin (Green Publisher Indonesia, 2025)
Cognitive development is a crucial aspect of a child's overall growth. This process refers to the stages in which the child undergoes changes that help them remember, understand, process information, and solve problems. One of the key factors in enhancing cognitive development in children is exclusive breastfeeding, defined as breastfeeding without any complementary foods since birth. This systematic review aims to determine the optimal duration of exclusive breastfeeding for cognitive development in children. This research is a systematic review focusing on journals published between 2012 and 2022, using the keywords (